TRANSFORMING BUSINESS: THE IMPACT OF DIGITAL INNOVATION ON MSME’s IN THE RIAU ISLANDS - Gani, Firman; Ardiansyah, Ardiansyah (MEASUREMENT : Jurnal Program Studi Akuntansi, 2025)
The rapid advancement of Information and Communication Technology (ICT) has paved the way for the Fourth Industrial Revolution, fostering economic and industrial development in the Riau Islands Province. The MSME sector is one that must adapt to technological advancements to ensure business sustainability, particularly due to the increasing number of competitors compelling entrepreneurs to innovate in order to succeed in this digital era. Furthermore, the Covid-19 pandemic has forced many MSMEs to transition from offline to online business models. This research aims to identify the responses and impacts of utilizing e-payment and e-commerce technologies on the performance of MSMEs in the Riau Islands Province. The study employs a descriptive methodology with quantitative analysis and sample selection is conducted using purposive sampling techniques. The findings reveal that the adoption of e-payment and e-commerce technologies plays a crucial role in enhancing the performance of MSMEs in the Riau Islands. This is reflected in the high percentage of MSMEs reporting increased revenue and various benefits after utilizing these platforms, such as the ability to conduct remote transactions with customers and broaden their marketing reach. However, several challenges persist, including issues with internet connectivity and a lack of knowledge regarding how to use and register on these platforms.